2010
DOI: 10.1016/j.micres.2009.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vibrio vulnificus in seafood, seawater and wastewater samples from a Mediterranean coastal area

Abstract: Vibrio vulnificus is an opportunistic human pathogen that may cause gastroenteritis, severe necrotizing soft-tissue infections and primary septicaemia, with a high lethality rate. Illness is associated to ingestion of seafood or to the exposure of contaminated water. The aim of this work was to determine the occurrence of V. vulnificus in water and seafood samples from a coastal area near the Mediterranean (Valencia, Spain). A TaqMan probe-based real-time PCR assay was optimised and applied to 22 sea water, 42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 34 publications
2
22
0
2
Order By: Relevance
“…V. vulnificus was found in one full body spa only. PCR of the vvhA gene according to Canigral et al [16] confirmed the MALDI-TOF identification.…”
Section: Microbiological Water Qualitymentioning
confidence: 82%
“…V. vulnificus was found in one full body spa only. PCR of the vvhA gene according to Canigral et al [16] confirmed the MALDI-TOF identification.…”
Section: Microbiological Water Qualitymentioning
confidence: 82%
“…E. coli, Shigella, Salmonella and Vibrio spp. have been the predominant pathogens linked to waterborne outbreaks in Africa [21,22], whereas certain clonal strains of these pathogens have been reported to survive conventional wastewater treatment processes [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Although Vibrio seems to be an important pathogenic agent in the NW Mediterranean (e.g. Canigral et al 2010, Lopez-Joven et al 2015, to the best of our knowledge no information on abundance of planktonic Vibrio (using culture independent methods) is available for Mediterranean waters.…”
Section: Introductionmentioning
confidence: 99%